2014
DOI: 10.1371/journal.pgen.1004432
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background Drives Transcriptional Variation in Human Induced Pluripotent Stem Cells

Abstract: Human iPS cells have been generated using a diverse range of tissues from a variety of donors using different reprogramming vectors. However, these cell lines are heterogeneous, which presents a limitation for their use in disease modeling and personalized medicine. To explore the basis of this heterogeneity we generated 25 iPS cell lines under normalised conditions from the same set of somatic tissues across a number of donors. RNA-seq data sets from each cell line were compared to identify the majority contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
235
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(262 citation statements)
references
References 35 publications
22
235
2
3
Order By: Relevance
“…31 It is now evident that differences in the quality of iPSC clones are largely due to technical variables relating to reprogramming approaches and culture conditions. 4,8,27,32 Additionally, some uncontrolled stochastic events during reprogramming undoubtedly influence gene expression and DNA methylation patterns in even functionally identical iPSC lines. Therefore, the evaluation of parameters that make iPSC line(s) indistinguishable from currently virtual but pre-existing ESCs, as well as the selection process, will be essential for identifying iPSC clones that are suitable for medical applications.…”
Section: Discussionmentioning
confidence: 99%
“…31 It is now evident that differences in the quality of iPSC clones are largely due to technical variables relating to reprogramming approaches and culture conditions. 4,8,27,32 Additionally, some uncontrolled stochastic events during reprogramming undoubtedly influence gene expression and DNA methylation patterns in even functionally identical iPSC lines. Therefore, the evaluation of parameters that make iPSC line(s) indistinguishable from currently virtual but pre-existing ESCs, as well as the selection process, will be essential for identifying iPSC clones that are suitable for medical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of genome-editing technologies such as transcription activator-like endonucleases (TALENs) and Cas9/clustered regularly interspaced short palindromic repeats (CRISPR) also offers the opportunity to introduce specific mutations in the genome of an hPSC line from which the phenotype and MK output are known using a specific differentiation protocol. The latter approach has the advantage to eliminate potential bias of interpretation due to inter-donor cell line variability [243].…”
Section: Disease Modellingmentioning
confidence: 99%
“…On the other hand, many other reports have demonstrated that no distinct differences (including differences in epigenetic memory) exist between ESCs and iPSCs [54,[74][75][76]. The number of cells used in such studies may influence conclusions.…”
Section: The Challenges Of Induced Pluripotent Stem Cells (A) Diversimentioning
confidence: 97%